2013
DOI: 10.4236/ojrm.2013.21002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low intensity pulsed ultrasound stimulation on bone regeneration in rat parietal bone defect model

Abstract: Purpose: Low intensity pulsed ultrasound stimulation (LIPUS) has been clinically applied to promote bone fracture healing in the orthopedic field. Thus, it is likely that LIPUS also stimulates bone regeneration in bone defects in the cranial-maxillofacial area. However, this has not been clearly proved. Furthermore, optimal time point and period of the application after the surgery has not been reported. The purpose of the present study was to evaluate the effect of LIPUS on bone regeneration in the rat pariet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…4 and 5). These findings were consistent with a previous study by Chen et al 13) who investigated the effect of LIPUS on bone regeneration in the rat parietal bone defects. These defects were analyzed with micro CT (µCT) and histological, demonstrating enhanced new bone formation fi lling the parietal defect whereby the newly-formed bone was thick and matured compared to the one in the control group.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4 and 5). These findings were consistent with a previous study by Chen et al 13) who investigated the effect of LIPUS on bone regeneration in the rat parietal bone defects. These defects were analyzed with micro CT (µCT) and histological, demonstrating enhanced new bone formation fi lling the parietal defect whereby the newly-formed bone was thick and matured compared to the one in the control group.…”
Section: Discussionsupporting
confidence: 83%
“…It reveals that LIPUS has positive eff ect on the healing of bone and the loss of marginal bone in the control group was contributed to not using US therapy 13,26,27) . The justifi cation of using LIPUS in this study is to accelerate the bone healing processes around the newly placed dental implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the amount of new bone formation in the bone defect was dependent on the time and period of LIPU application and was accelerated effectively at the second week after surgery. 23 As stated earlier, the second week after surgery is associated with the angiogenesis phase of the bone healing process. The intensity of LIPU and percentage of duty cycles should also be taken into account as factors influencing the healing results.…”
Section: Discussionmentioning
confidence: 97%
“…Ultrasound stimulation is considered to favour this phase as well. 23 The general clinical regimen for LIPU application is 20 min/day, 1 MHz sine waves repeating at 1 KHz, average intensity 30 mW/cm 2 , and pulse width 200 ms. However, there is no consensus regarding the therapeutic LIPU intensity.…”
Section: Discussionmentioning
confidence: 99%